The Impact of Demographic Change on Human Capital Accumulation - Michael Fertig; Christoph M. Schmidt; Mathias G. Sinning (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
This paper investigates whether and to what extent demographic change has an impact on human capital accumulation. The effect of the relative cohort size on educational attainment of young adults in Germany is analyzed utilizing data from the German Socio-Economic Panel for West-German individuals of the birth cohorts 1966 to 1986. These are the cohorts which entered the labor market since the 1980's. Particular attention is paid to the effect of changes in labor market conditions, which constitute an important channel through which demographic change may affect human capital accumulation. Our findings suggest that the variables measuring demographic change exert a considerable though heterogeneous impact on the human capital accumulation of young Germans. Changing labor market conditions during the 1980s and 1990's exhibit a sizeable impact on both the highest schooling and the highest professional degree obtained by younger cohorts.
Keywords: J11; J24; C25; 330; Demographic change; schooling; vocational training; Bildungsinvestition; Berufsbildung; Alternde Bevölkerung; Deutschland